A common variant in the glucokinase regulatory gene rs780094 and risk of nonalcoholic fatty liver disease: A meta-analysis - Zain, Shamsul Mohd; Mohamed, Zahurin; Mohamed, Rosmawati (Blackwell Publishing, 2014)
Background and Aim: Although studies have suggested that rs780094, a common variant in the glucokinase regulatory (GCKR) gene to be associated with type 2 diabetes, obesity, and their related traits, the genetic basis of the association between GCKR rs780094 and nonalcoholic fatty liver disease (NAFLD) is still being examined. This meta-analysis was performed to evaluate the effect strength caused by GCKR rs780094 on NAFLD. Methods: We searched Medline, PubMed, Scopus, and Embase for relevant articles published up to April 2014. Data were extracted, and summary estimates of the association between GCKR rs780094 and NAFLD were examined. Heterogeneity and publication bias were also examined. Results: This meta-analysis incorporated a total of 2091 NAFLD cases and 3003 controls from five studies. Overall, the pooled result indicated that the GCKR rs780094 was significantly associated with increased risk of NAFLD (additive: odds ratio (OR) 1.25, 95% confidence interval (CI) 1.14-1.36, P<0.00001). Analysis also revealed significant associations with different alternative genetic models for the inheritance: dominant, recessive, and homozygote (OR 1.40, 95%CI 1.23-1.61, P<0.00001; OR 0.79, 95% CI 0.68-0.91, P=0.001, and (OR 1.27, 95% CI 1.10-1.47, P=0.001, respectively), but not the heterozygote model. Population subgroup analysis demonstrated similar effect size in both Asians and non-Asians (OR 1.27, 95%CI 1.12-1.45, P=0.0003 and OR 1.22, 95%CI 1.10-1.37, P=0.0003, respectively). Conclusions: Our meta-analysis provides evidence of significant association between GCKR rs780094 and risk of NAFLD. Similar effect size was demonstrated in both Asian and non-Asian populations.